Suspension of the Main Proceedings and Referral for a Preliminary Rul-ing. Gloss to the Judgment of the CJEU in Case C-176/22, Bk And ZhP, of 17 May 2023 - Liakopoulos, Dimitris (Review of European and Comparative Law, 2024)
The preliminary reference as an appeal of the Court of Justice of the European Union presents many complexities and complicated interpretations over time, given that we have a national judge in the scene of the appeal process, often creating problems but also solutions for greater effectiveness of the law of the European Union and respect for domestic law. The preliminary ruling aims to resolve disputes between internal jurisdictions and evaluate compatibility with EU law, especially in the national procedural sector. Ensuring a postponement of the EU and, above all, protecting the rights of individuals in a concrete, complete and effective way is still questionable research, not so much on a theoretical level but also on a procedural one.